Behavioral and Educational Characteristics of Students with Behavioral and Emotional Disorders in Jordan - AlWreikat, Hussein Abdallah; Smadi, Jamil Mahmoud; Alabdallat, Bassam Moqbel (Dirasat: Educational Sciences, 2022)
Objectives: The current study aims to identify behavioral and educational characteristics of students with behavioral and emotional disorders from the point of view of their parents. Methods: A descriptive approach was employed. The study sample consisted of (1298) students with behavioral and emotional disorders aged between (5-15) years, selected through teachers' assessments. A scale of behavioral and educational characteristics for students with disorders was built. Behavior and emotionality are made up of five dimensions: inability to learn, inappropriate behavior in social situations, relationship problems with colleagues and teachers, feelings of sadness and depression, and physical symptoms and fears. Results: The results show that the overall average of behavioral and educational characteristics scale for students with behavioral and emotional disorders was low. The results indicate that there are statistically significant differences in the total score of behavioral and educational characteristics scale due to gender in favor of males, and due to stage in favor of the upper school stage. Conclusions: The study finds that it is necessary to support families of children with behavioral and emotional disorders with information about the disorder and how to deal with it.